Where East Meets West: Appropriating the Islamic Encounter for a Spiritual-Cultural Revival, rev. ed. by Mona Abul-Fadl (Herndon, VA: International Institute of Islamic Thought, 2010. hbk. and pbk. 95 pages.) (American Journal of Islam and Society, 2011)
This short and concise book is presented as an important brick in the foundationof what had been designated the “Western Thought Project.” AsMona Abul-Fadl has indicated, the aim of this project was to encouragean “active” and “critical” presence of the Muslim intellect as well as promotingthe “Islamization of knowledge” (vii). This was rendered necessaryin light of the dilemmas facing Muslims everywhere as they strive toreconcile their religious conscience with the historical realities of a modernWestern consciousness. Abul-Fadl optimistically and ambitiously perceivespossibilities of shaping a “Muslim discourse on conscience” withina cooperative framework with the West ‒ in order, as she put it, to “evolvetogether the terms of a new global consciousness which is inclusive” (xi).This presumably would entail a dialogue, not with the West in general, butwith a particular variant of it that harbors religious commonalities withIslam in terms of the givens of God, humans, history, and revelation. Abul-Fadl seeks to change the terms of the encounter from the political and theeconomic to the intellectual and the cultural (xiv). Summoning the intellectualcommunity, primarily of Muslims but non-Muslims as well, is theprerequisite for the bid to renegotiate the terms of this proposed global encounter,and she asserts that the “fate of our civilization lies in the balanceof culture, not power” (1). Such a “simple truth” is the premise of her study ...